Pengurusan organisasi - Zafir Mohd. Makhbul, author 624122; Mohd. Hizam Hanafiah, author 442468; Fazilah Mohamad Hasun, author 356815 (Singapore : Cengage Learning Asia Pte. Ltd., 2009)
Includes bibliographical and references